2005
DOI: 10.1071/ah050025
|View full text |Cite
|
Sign up to set email alerts
|

Hurdles to health: immigrant and refugee health care in Australia

Abstract: Refugees and asylum seekers face a number of barriers to accessing health care and improved health status. These include language difficulties, financial need and unemployment, cultural differences, legal barriers and a health workforce with generally low awareness of issues specific to refugees. Importantly, current Australian government migration and settlement policy also impacts on access to health and health status. An adequate understanding of these 'hurdles to health' is a prerequisite for health provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(90 citation statements)
references
References 12 publications
3
85
1
1
Order By: Relevance
“…Australian and overseas literature has highlighted language and cultural differences, distrust of health professionals, a lack of health information, poor understanding of the health care system, an often-undertrained workforce and financial limitations as impacting on refugees' ability to access health care (Finney Lamb and Smith 2002;Davidson et al 2004;Murray and Skull 2005;Sheikh-Mohammed et al 2006;Henderson and Kendall 2011). These issues were mirrored in the comments of providers, as they discussed the barriers they experienced in providing care, highlighting the way in which patients and health care providers are struggling to overcome these issues together.…”
Section: Discussionmentioning
confidence: 99%
“…Australian and overseas literature has highlighted language and cultural differences, distrust of health professionals, a lack of health information, poor understanding of the health care system, an often-undertrained workforce and financial limitations as impacting on refugees' ability to access health care (Finney Lamb and Smith 2002;Davidson et al 2004;Murray and Skull 2005;Sheikh-Mohammed et al 2006;Henderson and Kendall 2011). These issues were mirrored in the comments of providers, as they discussed the barriers they experienced in providing care, highlighting the way in which patients and health care providers are struggling to overcome these issues together.…”
Section: Discussionmentioning
confidence: 99%
“…interpreters or group facilitators) was recognised as supportive by the immigrants themselves. As in other studies, 5,6 this review identified issues around factors such as accessibility, language barriers and the complexity of systems. Similar to a report of other immigrant studies, 60 theme 2 demonstrates that immigrants often did not feel confident, secure and able to take the initiative in seeking information.…”
Section: Discussionmentioning
confidence: 98%
“…Language problems may affect individuals at any stage of the process of seeking health care and often have a detrimental effect on satisfaction even before a person sees a doctor. For the Sudanese community, for example, it may be difficult to make an appointment (which usually must be done by phone), determine what kind of service they need, and figure out where to get it (see Murray and Skull, 2005;Sheikh-Mohammad et al, 2006).…”
Section: The Arabic Speaking Community In Melbournementioning
confidence: 99%